Analisis Kesesuaian Kawasan Agrowisata Herbal di Desa Seberaya - Munthe, Theodora Ginting; Lubis, Zulkarnain; Lubis, Yusniar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The study of the suitability of the area to be used as herbal agro-tourism is quite important in supporting business sustainability and village development efforts in the future.  One of the villages in Tanah Karo with potential is Seberaya, where Seberaya Village has an agrarian area and has a beautiful natural panorama. The purpose of this research is to analyse the suitability of the area based on the potential of Seberaya Village for the development of herbal agro-tourism areas based on the People's Nucleus Plantation (PIR) pattern.  The research was conducted through 5 stages, namely: 1). Preparation; 2). Data collection; 3). Analysis of area potential; 4). Data analysis; 5). Preparation of recommendations. Based on the results of data analysis for the Attitude Scale Score (SSS), a value between 434 - 313 was obtained, with an average of 4.29 - 3.91, meaning that this was strongly agreed. It is concluded that Seberaya Village is very feasible to be developed into a herbal agro-tourism area because it has aspects of natural resources and socio-culture that are very supportive.